Shape-Preservation of the Four-Point Ternary Interpolating Non-stationary Subdivision Scheme - Ashraf, Pakeeza; Sabir, Mehak; Ghaffar, Abdul; Nisar, Kottakkaran Sooppy; Khan, Ilyas (Frontiers in Physics, 2020)
In this paper, we present the shape-preserving properties of the four-point ternary non-stationary interpolating subdivision scheme (the four-point scheme). This scheme involves a tension parameter. We derive the conditions on the tension parameter and initial control polygon that permit the creation of positivity- and monotonicity-preserving curves after a finite number of subdivision steps. In addition, the outcomes are generalized to determine conditions for positivity- and monotonicity-preservation of the limit curves. Convexity-preservation of the limit curve of the four-point scheme is also analyzed. The shape-preserving behavior of the four-point scheme is also shown through several numerical examples.